PENGARUH SOFT SKILL DAN PENGALAMAN MAGANG TERHADAP KESIAPAN KERJA MAHASISWA FEB UHO - Muhammad Syarif; Wahyuni Rahma (STIE ENAM ENAM KENDARI, 2025)
This study aims to analyze the influence of soft skills and internship experience on the work readinessof students at the Faculty of Economics and Business, Halu Oleo University. This study uses aquantitative method with multiple linear regression analysis to examine the relationship betweenvariables. Data were collected through a survey using a questionnaire distributed to 90 final-yearstudents at the Faculty of Economics and Business, Halu Oleo University who had participated in aninternship program. The results of the study indicate that soft skills have a positive and significanteffect on work readiness, meaning that the higher the level of students' soft skills, the higher theirwork readiness. In addition, internship experience also has a positive and significant effect onstudents' work readiness, meaning that the higher the student's internship experience, the higher theirwork readiness. Simultaneously, both variables, namely soft skills and internship experience,contribute significantly to improving work readiness. These findings confirm that improving soft skillsthrough education and organizational activities, as well as strengthening structured internshipprograms, are key to preparing graduates who are ready to compete in the world of work.